2009
DOI: 10.1099/vir.0.014183-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a novel species of flavivirus and a new strain of Culex flavivirus (Flaviviridae) from a natural mosquito population in Uganda

Abstract: The genus Flavivirus, which contains approximately 70 single-stranded, positive-sense RNA viruses, represents a unique model for studying the evolution of vector-borne disease, as it includes viruses that are mosquito-borne, tick-borne or have no known vector. Both theoretical work and field studies suggest the existence of a large number of undiscovered flaviviruses. Recently, the first isolation of cell fusing agent virus (CFAV) was reported from a natural mosquito population in Puerto Rico, and sequences re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
0
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(136 citation statements)
references
References 36 publications
5
122
0
9
Order By: Relevance
“…Images of thin sections were observed under a transmission electron microscope (JEM 1230; JEOL). The supernatant was also harvested and subject to negative staining EM as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
“…Images of thin sections were observed under a transmission electron microscope (JEM 1230; JEOL). The supernatant was also harvested and subject to negative staining EM as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
“…It was the first ''insect flavivirus'' (e.g viruses that propagate only in mosquito cells but not in mammalian cells) discovered. To date, six other ''insect flaviviruses'' have been described: Kamiti River virus (KRV), isolated from field collected Aedes macintoshi in Africa in 2003 (Crabtree et al 2003); Culex Flavivirus (CxFV), isolated mainly from Culex mosquitoes in Japan, Indonesia (Hoshino et al 2007), Guatemala (Morales-Betoulle et al 2008), México (Farfan-Ale et al 2009), United States, Trinidad (Kim et al 2009), and Uganda (Cook et al 2009); Aedes Flavivirus (AEFV), isolated from Aedes albopictus mosquito in Japan (Hoshino et al 2009); Quang Binh virus (QBV) isolated from Culex tritaeniorhynchus in Vietnam (Crabtree et al 2009); Nakiwogo virus (NAKV) isolated from Mansonia africana nigerrima in Uganda (Cook et al 2009); and Calbertado virus detected mainly in Cx. tarsalis mosquitoes in Canada (Pabbaraju et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…CxFV was first isolated from Culex pipiens Linnaeus mosquitoes in Japan (Hoshino et al 2007) but appears to have a global distribution, with additional variants identified in other Culex species and subspecies from Mexico, Uganda, Trinidad, and the United States (Morales-Betoulle et al 2008, Blitvich et al 2009, Cook et al 2009, Farfan-Ale et al 2009, Kim et al 2009). The insect-specific designation of CxFV derives from the observation that it has been cultured in the laboratory only in mosquito cell lines and, additionally, that it has been identified in many natural populations of Culex mosquitoes (Hoshino et al 2007).…”
Section: Introductionmentioning
confidence: 99%